Comparison of Anti-Salmonella Typhi IgM Examination Results with SD Bioline and Tubex TF. Methods - Herlinawati Herlinawati; Resna Hermawati; I Gede Angga Adyana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Salmonella typhi is a gram-negative bacterium that is an intracellular facultative pathogen, which enters the human body and causes an acute systemic infectious disease called typhoid fever. Among the laboratory tests used to detect the presence of anti-Salmonella typhi IgM in serum are SD Bioline and Tubex TF. This study aims to determinecomparison of the results of the anti-Salmonella typhi IgM examination with the SD Bioline and Tubex TF methods. Analytical observation with cross-sectional design. This research was conducted in RSUD DR. Soedjono Selong. The time of the study was January-April 2022. The sample of this study was patients who underwent typhoid fever examination who were hospitalized at RSUD DR. Soedjono Selong as many as 60 people. This research uses the methodconsecutive sampling,Anti-Salmonella typhi IgM was examined with the SD Bioline kit using the immunochromatography method and the TUBEX TF kit using the Inhibition Magnetic Binding Immunoassay (IMBI) method. Data analysis was performed using SPSS, namely univariate test, and bivariate test with Chi-square. There were 26 (43.3%) male and 34 (56.7%) female patients. The youngest is 2 years old and the oldest is 64 years old with an average age of 25 years ± 19 years. Of the total 60 patients examined with SD Bioline, 5 (8.3%) were positive and 55 (91.7%) were negative. Meanwhile, examination with TUBEX TF found 3 (5%) positive people and 57 (95%) negative people. And there was a significant comparison between the results of the SD Bioline and Tubex TF examination with a value (p = 0.000) and a low level of conformity was obtained with a Kappa value of 0.000. A comparison of the results of the IgM anti-Salmonella typhi examination was obtained using the SD Bioline and Tubex TF . methodswith a very low degree of conformity.